THE INFLUENCE OF INNOVATIONS ON THE MANAGEMENT OF TECHNOLOGICAL DEVELOPMENT IN THE CROP INDUSTRY - VLASENKO, Tetiana; LARINA, ТETIANA; DZIUBANOVSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
One of the leading industries is crop production. It is the main source for the production of vital products, as well as the raw material base for their production. The amount of production depends proportionally on the development of this industry. Thus, production volumes should fully meet the needs of the population. For the effective development of the field of crop production at this stage, it is necessary to constantly improve the existing and introduce new technologies for the production of agricultural products; fundamentally change economic relations between producers and consumers of science-intensive products; form an innovative state policy aimed at an innovative way of developing the country's agrarian economy. Modern agricultural enterprises work completely differently than those of a few decades ago, primarily due to advances in technology, including sensors, devices, machines and information technologies. In the conditions of the constant increase in the price of energy resources and raw materials for the production of mineral fertilizers, the presence of a shortage of organic fertilizers, the reduction of areas suitable for growing agricultural crops, due to the strengthening of erosion processes and desertification caused by global warming, the problem of finding the most effective ways of managing profitability and reducing the cost of living is becoming urgent agricultural products. One of the ways of its successful solution is the introduction of innovative technologies in the field of land use. Digitization is turning agriculture into a high-tech sector of the economy, processing massive amounts of big data coming from numerous sensors installed in the field, on the farm, agricultural machinery, from weather stations, satellites and other systems. These advanced devices, precision farming, new technologies and robotic systems enable businesses to be more profitable, more efficient, safer and more environmentally friendly. The use of innovations in agriculture ensures an increase in labor productivity, a decrease in the cost price and an increase in the quality and competitiveness of products, contributes to solving the problem of food security in the country and increasing the sustainability of agricultural enterprises.
Keywords: innovations; micro level; technique; technologies; management; crop production